Intellectual capital and firm performance and productivity: Empirical evidence from Malaysian stock exchange / Amrizah Kamaluddin ... [et al.]. - Kamaluddin, Amrizah; Ibrahim, Muhd Kamil (2005)
The research explores the intellectual capital value among listed companies in Malaysia by applying Market-to-Book Value Model and examines empirically whether intellectual capital value contributes to firm financial performance and productivity. The research also gauge whether there is any relationship between intellectual capital and type of industry. Evidenced with samples of companies listed on the Main Board of Malaysian Stock Exchange it was found that in the year 2000 and 2001, there are significant influence between profitability performances with intellectual capital.